Merging process of U-turns at uncontrolled median openings under mixed traffic conditions - Gourab Sil; Smruti Sourava Mohapatra; Partha Pratim Dey; Satish Chandra (Transport, 2018)
At an uncontrolled median opening, the limited priority situation and the high degree of heterogeneity in traffic stream make the merging manoeuvre of U-turning vehicles very much complex. This study is an attempt to understand this merging manoeuvre. The different types of merging manoeuvres have been identified in the field and accordingly classified into different categories. Depending upon the number of vehicles that can merge all together into the opposing through traffic by accepting a single gap, the merging has been classified into two types: single entry merging and multiple entry merging. On the other hand, based on the situation of priority of movement, the merging process is divided into another two categories: ideal merging and forced merging. More explicitly, the ideal merging is split into free merging and Swift Merging (SM). In addition, the forced entry merging is categorized into Gradual Merging (GM) and Aggressive Merging (AM). Time distance diagrams for different types of merging are presented for their better understanding. Field data collected at seven median openings located on various 6-lane divided urban roads are used to analyse different types of merging in a mixed traffic situation. All vehicles plying on the road are divided into 5 categories such as car, motorized two-wheeler (2-W), motorized three-wheeler (3-W), Sports Utility Vehicle (SUV), and Light Commercial Vehicle (LCV) and the merging behaviour of these categories of vehicles have been studied. The effect of influencing parameters like opposing traffic volume and delay on merging are investigated. Mathematical relations are developed between Merging Time (MT) of a vehicle type and the opposing traffic volume. To address the effect of Service Delay (SD) on the MT of a vehicle, models are proposed between SD and MT for all the five categories of vehicles. The two types of merging; gradual and swift are prominently observed in field. The time required by different categories of vehicles for these two merging at various traffic volume levels are determined. Finally, two-tailed t-test is conducted to see if the MT for the two different types of merging is statistically different.